DISKURSUS BAHASA TUHAN DALAM PERSPEKTIF STRUKTURALISME LINGUISTIK MODERN - Tauhedi As'ad; Munif Shaleh (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
God's language is not reached by human nature because God's language enters the parole area which cannot be verified, because parole language is God's revelation that cannot be intervened by the human language system. This model, is very new to be continued in the approach of Islamic studies, especially modern linguistic studies developed by Ferinand De Sausure, then by Paul Ricouer as the post structuralist father. However, if you re-understand the language of God in the perspective of modern linguistics as an approach in Islamic thought, then there is a problem that is addressed, namely the existence of God's Revelation which wraps into Arabic, then the corpus is formalized as a manuscript written by humans. Then God's revelation will lose the existence of authority as the owner of the message of revelation so that the Koran that is read now by all Muslims is no longer sacred and authentic. This is the revelation imprisoned by Arabic as the Ottoman Manuscripts.